Perancangan Interior Music Lesson House di Bali - Eunike Tiffani Lomena (Intra, 2014)
Music Lesson House is a project where people can learn to play music regardless of age and free to express their own taste of music. Music Lesson House gives a comfortable and appropriate facility to fully develop their music creativity. Additionally, music can train and balance the brain to be able to do well. Beside the music facilities for normal people, one of the advantages of this House Music Lesson is music therapy facilities for people with special needs, aged 3 to 14 years. Music therapy can boost your confidence and help control measures among hyperactive children who have special needs and can create mental and behavioral changes are significant. Music Lesson House performing to the theme of the Joy of Music to create an arrangement of space for those who want to relax and let go of tired of the daily routine activities. The application of the arrangement embodied space, shape, and color and material acoustic support to build the atmosphere so that visitors can experience something different and satisfaction with the music.